Analysis of the cytopathological reports achieved and not removed from a Centro de Parto Natural (CPN) in Fortaleza-Ce: a documentary study - Thais Marques Lima; Ana Rita Pimentel Castelo; Roberta Grangeiro de Oliveira; Líllian de Queiroz Costa; Micaele Cardoso Tavares; Juliana Maria Vieira de Santiago; Ana Karina Bezerra Pinheiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The research aimed to examine the cytopathological reports made and not removed from a Centro de Parto Natural (CPN) in Fortaleza-Ce. It is a documentary study, with retrospective quantitative approach. Data collection was through the analysis of 237 reports of cervical examinations performed between the years 2005 to 2007 and not received by the women until May 2008. The results showed that most women have between 12 and 79 years. In relation to microbiological findings (27%) had Lactobacilli sp, (20.25%) cocci and bacilli, (5.9%) candidiasis, (26.58%) Gardnerella vaginallis and (3.37%) Trichomonas vaginalis. The majority (44.3%) had moderate inflammatory process, (33.8%) mild inflammation and (21.9%) severe inflamation. Gardnerella / Mobiluncus was present in 28.6% of cases of moderate inflammation and in 26.9% of cases of severe inflammation, while 87.5% of reports that showed Trichomonas vaginalis had severe inflammation. Among the reports analyzed, four cases were diagnosed with NIC I and one case of NIC III (1.1%). Thus, educational strategies in health and the active search become essential to ensure the return of women to receive the results, enabling the continuity of treatment and prevention of uterine cervical neoplasms.